Metastatic nasopharyngeal carcinoma presenting as an isolated breast mass: A diagnostic pitfall and a review of literature - Trupti Pai; Nita Nair; Gauri Pantvaidya; Kedar Deodhar; Tanuja Shet (Wolters Kluwer Medknow Publications, 2017)
Metastases to breast are much rarer than primary breast tumors. We now present a case of 45-year-old female, who presented with an isolated breast mass. A positron emission tomography-computed tomography (PET-CT) done revealed hypermetabolic right breast nodules, soft tissue deposits, and multiple nodal involvement. The biopsy from the breast and axillary lymph node showed dense lymphoid infiltrate and was interpreted initially as granulomatous inflammation. However, the lumps were hard and suspicious for primary breast cancer, so an immunohistochemistry for cytokeratin was performed which highlighted the epithelial cell clusters masked within the inflammatory infiltrate and the diagnosis of undifferentiated carcinoma, lymphoepithelioma-like was made. After the diagnosis was made, it was realized that the patient had been treated earlier for a nasopharyngeal carcinoma (NPC). The in situ hybridization (ISH) test for Epstein-Barr virus-encoded RNA ISH was positive in the tumor cells, and hence, a diagnosis of metastatic NPC was finally made. The patient subsequently developed extensive nodal, skeletal, and soft tissue metastatic disease but was alive till September 2015. Although extremely rare, metastatic NPC can occur in the breast and the above case highlights that it mimics an inflammatory lesion. This case highlights the importance of the multidisciplinary approach for appropriate tumor diagnosis and patient management.